Women's access to agriculture extension amidst COVID-19: Insights from Gujarat, India and Dang, Nepal - Alvi, Muzna; Barooah, Prapti; Gupta, Shweta; Saini, Smriti (Elsevier, 2021)
COVID-19 induced lockdowns have had far reaching impacts on the rural sector, particularly on women farmers. These impacts have been exacerbated by lack of access to reliable and timely agriculture information. Using panel phone survey data from India and Nepal, we study how women's access to agricultural extension was impacted by the lockdowns and its effect on agricultural productivity. We find that women's already low access to formal extension was reduced further, leading to an increased reliance on informal social networks. In both countries, nearly 50% farmers reported negative impacts on productivity due to inaccessibility of information during the lockdown. In India, we find that access to formal extension is mediated by crop type, geographic location and caste identity. We discuss ways in which extension systems in India and Nepal can be made more inclusive and resilient to future crisis, including by adapting group and community-based approaches to post-pandemic best practices.